Assessment of outcome of distal radius inta-articular fractures using wrist-spanning mini-fixator in distraction - Patel, Saurin J.; Merawat, KirtiDhavaj I.; Singh, Harpreet; Bhavsar, Parth B. (International Journal of Research in Orthopaedics, 2019)
Background: The distal radius fractures are complex injuries. There are many treatment options for these fractures. The benefits of external fixation with mini fixator have been seen in many studies. In our study, the distal radius fracture belonging to type B and C of AO classification were treated with wrist spaning mini extrernal fixator with/without additional k wires. We wish to analyse the functional outcome and to determine any complications of this procedure. Methods: 20 patients were included in this study and were followed up for up to 6 months postoperatively. We assessed pain using VAS score at 6 weeks follow-up and the outcome of each patient was assessed using Mayo wrist score post-operatively on follow-up at 3 months and 6 months. Results: Predominance towards males and left upper limb was observed in our study. At the end of six months, the range of motion as assessed according to the criteria given by Mayo wrist score, excellent results (MWS>=90) were seen in 4 patients (20%), good results (MWS 80-89) were seen in 12 patients (60%),and fair (MWS 70-79) in 4 patient (20%). At the end of result, significant reduction in terms of pain, wellbeing, personal life, social life, lifting, travelling and sleeping was seen. Conclusions: Predominance towards males and left upper limb was observed in our study. At the end of six months, the range of motion as assessed according to the criteria given by Mayo Wrist Score, excellent results (MWS>=90) were seen in 4 patients (20%), good results (MWS 80-89) were seen in 12 patients (60%),and fair (MWS 70-79) in 4 patient (20%). At the end of result, significant reduction in terms of pain, wellbeing, personal life, social life, lifting, travelling and sleeping was seen.